Elevation of circulating TNF receptor 2 in cancer: A systematic meta-analysis for its potential as a diagnostic cancer biomarker - Kartikasari, Apriliana E. R.; Cassar, Emily; Razqan, Mohammed A. M.; Szydzik, Crispin; Huertas, Cesar S.; Mitchell, Arnan; Plebanski, Magdalena (Frontiers in Immunology, 2022)
High Tumor Necrosis Factor Receptor 2 (TNFR2) expression is characteristic of diverse malignant cells during tumorigenesis. The protein is also expressed by many immunosuppressive cells during cancer development, allowing cancer immune escape. A growing body of evidence further suggests a correlation between the circulating form of this protein and cancer development. Here we conducted a systematic meta-analysis of cancer studies published up until 1st October 2022, in which the circulating soluble TNFR2 (sTNFR2) concentrations in patients with cancers were recorded and their association with cancer risk was assessed. Of the 14,615 identified articles, 44 studies provided data on the correlation between cancer risk and the level of circulating sTNFR2. The pooled means comparison showed a consistently significant increase in the levels of sTNFR2 in diverse cancers when compared to healthy controls. These included colorectal cancer, ovarian cancer, breast cancer, non-Hodgkin’s lymphoma, Hodgkin’s lymphoma, lung cancer, hepatocarcinoma, and glioblastoma. In a random-effect meta-analysis, the cancer-specific odd ratios (OR) showed significant correlations between increased circulating sTNFR2 levels and the risk of colorectal cancer, non-Hodgkin’s lymphoma, and hepatocarcinoma at 1.59 (95% CI:1.20-2.11), 1.98 (95% CI:1.49-2.64) and 4.32 (95% CI:2.25-8.31) respectively. The overall result showed an association between circulating levels of sTNFR2 and the risk of developing cancer at 1.76 (95% CI:1.53-2.02). This meta-analysis supports sTNFR2 as a potential diagnostic biomarker for cancer, albeit with different predictive strengths for different cancer types. This is consistent with a potential key role for TNFR2 involvement in cancer development.